English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

tan a/1- cot a+cot a/1-tan a =1+tan a+cot a=1+ sec a+ cosec a
is there any way to prove this quickly?

2006-12-18 20:24:00 · 10 answers · asked by srinath 2 in Science & Mathematics Mathematics

10 answers

If you write the left side in
terms of sin(a) and cos(a) and combine the resulting fractions
over common denominators in the numerator and denominator, and
then simplify, you will obtain an expression which can be reduced
to the second expression 1 + tan(a) + cot(a), so the first
equality expresses an identity, not an equation to be solved.
Neither of the first two expressions is identically 0.

The third expression is not equal to the other two for all a.
For example, if a = pi/4, 1+tan(a)+cot(a) = 3, while
1 + sec(a) + COSEC(a) = 2*sqrt(2)+1 .

IF YOU NEED FURTHER EXPLANATION REGARDING THIS SUM YOU CAN GO TO

2006-12-19 02:23:16 · answer #1 · answered by bookworm 2 · 0 0

LHS = tan a /(1-cot a) + cot a /(1-tan a)
multiply both num and den by tan a
= tan^2 a /(tan a - 1) + 1/tan a (1- tan a)
= (tan ^3 a - 1)/((tan a -1)tan a)

= ((tan ^3 a -1 )/(tan a - 1))/ tan a

= (tan ^ 2 a + tan a + 1)/ tan a (using (x^3-y^3) formula
= tan a + 1 + cot a

= middle term

= 1 + sin a/cos a + cos a/ sin a
= 1 + (sin ^2 a + cos^2 a)/ sin a cos a
= 1 + 1/ sin a cos a
= 1 + cosec a sec a
not RHS

2006-12-18 21:30:12 · answer #2 · answered by Mein Hoon Na 7 · 0 1

1. Solve for left side
(tan a/1- cot a)+(cot a/1-tan a)
=tan a/(1- (1/tan a)) + (cot a/1-tan a)
=tan a/((tan a - 1)/ tan a) + (cot a/1-tan a)
=tan^2 a / (tan a - 1) + (cot a/1-tan a)
= -tan^2 a/ (1 - tan a) + (cot a/1-tan a)
= (cot a - tan^2 a) / (1-tan a)
1+tan a+cot a
2. Solve for middle
1+tan a+cot a
=1+tan a+cot a * (1-tan a)/(1-tan a)
=(1-tan a + tan a - tan^2 a + cot a - tan a cot a)/(1-tan a)
=(1 -tan^2 a + cot a -1)/(1-tan a)
=(cot a - tan^2)/(1-tan a)
So... Left and middle are equal...
3. Solve for Right
1+ sec a+ cosec a
= I haven't figured it out yet...
Wow... he's good...

2006-12-18 21:04:35 · answer #3 · answered by Elicasel 3 · 0 1

The right hand side of the question is wrong. When we convert the ratios of left hand side into sin & cos & simplify it, we get,

1+ cosecA.secA and not 1+cosecA+secA

2006-12-18 20:39:49 · answer #4 · answered by shailendra s 3 · 0 0

in the first part you have 0. something is missing. Check to see if you typed it in right.

2006-12-18 20:36:03 · answer #5 · answered by Monica G 1 · 0 0

dont u think u are missing something u are missning brackets do it first and compleat ur quistion otherwise it will not be eaqual

2006-12-18 20:37:51 · answer #6 · answered by coolsober 2 · 0 0

Not equal so no solutions

2006-12-19 00:59:04 · answer #7 · answered by Kenneth Koh 5 · 0 0

Yes. There is.
But I forgot what it is, because I don't have to take math anymore.

2006-12-18 20:30:07 · answer #8 · answered by ladybugewa 6 · 0 2

tana/1-cota + cota/1-tana
=sin^2a/cosa(sina-cosa) + cos^2a/sina(cosa-sina)
=sin^3a-cos^3a/sinacosa(sina-cosa)
=sin^2a+cos^2a+sinacosa/sinacosa
=1+tana+cota

2006-12-18 22:07:24 · answer #9 · answered by tarun g 1 · 0 0

Sorry , they r not equal.....

2006-12-18 20:31:00 · answer #10 · answered by @rrsu 4 · 0 0

fedest.com, questions and answers